Analisa Kinerja Jaringan W-LAN Pada Perangkat Access Point 802.11/g (Studi Kasus Fakultas Teknik Universitas Riau) - Eko Prasetyo Manru; Febrizal Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Quality of Service is a mechanism of network that enables applications or service to operate as expected.This journal discusses about the performance analysis of wireless LAN consisting of some parameters i.e.throughput , packet loss , delay , and jitter. Method used in the research was action research. Overall, themeasurement of wireless LAN best average performance at the Faculty of Engineering, University of Riauwas obtained in access point Akademika _ 04 at daytime measurement (13.00-15.30) at a distance of 5meters by throughput 383 kbps, packet loss 4 % , delay 96 ms , jitter 19 ms and signal strength -43 dbm. Theworst average performance was obtained in access point Akademika _ 01 at morning time measurement (09.00-11.30 ) at a distance of 20 meters by throughput 110 kbps , packet loss 48 %, delay 433 ms , jitter 72ms and strong signal -67 dbm..Keywords : wireless LAN, Quality of service.